2010
DOI: 10.1152/ajpheart.00212.2010
|View full text |Cite
|
Sign up to set email alerts
|

Diazoxide potentiates mesenchymal stem cell survival via NF-κB-dependent miR-146a expression by targeting Fas

Abstract: Suzuki Y, Kim HW, Ashraf M, Haider HKh. Diazoxide potentiates mesenchymal stem cell survival via NF-B-dependent miR-146a expression by targeting Fas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 33 publications
2
63
0
Order By: Relevance
“…shown to be a target of miR-146a in bone marrow-derived mesenchymal stem cells (Suzuki, et al 2010). A connection between miR-21 and miR-146a and female sex steroids can be emphasized, as it has been demonstrated that both of these miRs are highly present in the plasma of breast cancer patients (Kumar, et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…shown to be a target of miR-146a in bone marrow-derived mesenchymal stem cells (Suzuki, et al 2010). A connection between miR-21 and miR-146a and female sex steroids can be emphasized, as it has been demonstrated that both of these miRs are highly present in the plasma of breast cancer patients (Kumar, et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The luciferase assay was performed using the Dual-Luciferase Reporter Assay Kit (Promega) as previously described. 24 Microarray analysis B cells of the WT and miR-146a TG mice were isolated from lymph nodes with an untouched magnetic separated assay, and dead cells were depleted with the Dead Cell Removal Kit (Miltenyi Biotec). The cells were lysed with TRIzol reagent (Invitrogen).…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%
“…Recently, diazoxide has also featured in a number of studies by Ashraf's group to precondition stem and progenitor cells. They have shown that ex vivo preconditioning with diazoxide can promote skeletal myoblasts Niagara PC (Afzal et al, 2010;Suzuki et al, 2010) survival both in vitro and in vivo post-transplantation. Furthermore, transplantation of these preconditioned cells into the infarcted myocardium was associated with smaller infarct size, improved LV function, myogenic differentiation and angiogenesis (Afzal et al, 2010;Haider et al, 2010;Niagara et al, 2007).…”
Section: Diazoxidementioning
confidence: 99%
“…The activation of NFκB in diazoxide preconditioned MSCs was subsequently implicated to regulate the expression of miR-146a, which in turn acts as a negative regulator of the Fas gene, a death receptor of apoptosis (Suzuki et al, 2010).…”
Section: Diazoxidementioning
confidence: 99%